2010
DOI: 10.1038/aps.2010.83
|View full text |Cite
|
Sign up to set email alerts
|

Geniposide inhibits high glucose-induced cell adhesion through the NF-κB signaling pathway in human umbilical vein endothelial cells

Abstract: Aim: To investigate whether geniposide, an iridoid glucoside extracted from gardenia jasminoides ellis fruits, inhibits cell adhesion to human umbilical vein endothelial cells (HUVECs) induced by high glucose and its underlying mechanisms. Methods: HUVECs were isolated from human umbilical cords and cultured. The adhesion of monocytes to HUVECs was determined using fluorescence-labeled monocytes. The mRNA and protein levels of vascular cell adhesion molecule-1 (VCAM-1) and endothelial selectin (E-selectin) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
23
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(26 citation statements)
references
References 37 publications
3
23
0
Order By: Relevance
“…The lack of insulin or IGF1 effects is in agreement with observations made with HUVECs (Balaram et al 1997, Montagnani et al 2002, Madonna et al 2004. High glucose concentrations (20 mmol/l or higher) was found to increase E-selectin expression in HUVECs after incubation for 24 h or longer (Zheng et al 2008, Wang et al 2010. We incubated our cells in high concentration glucose for 4 h, which could explain the absence of a glucose effect.…”
Section: Discussionsupporting
confidence: 92%
“…The lack of insulin or IGF1 effects is in agreement with observations made with HUVECs (Balaram et al 1997, Montagnani et al 2002, Madonna et al 2004. High glucose concentrations (20 mmol/l or higher) was found to increase E-selectin expression in HUVECs after incubation for 24 h or longer (Zheng et al 2008, Wang et al 2010. We incubated our cells in high concentration glucose for 4 h, which could explain the absence of a glucose effect.…”
Section: Discussionsupporting
confidence: 92%
“…Since oxidative stress is an important determinant of endothelial dysfunction and vascular injury and intracellular ROS potently stimulate EC adhesion molecule expression (25,26), we hypothesized that dasatinib may lead to increased intracellular ROS in pulmonary ECs, thereby inducing EC apoptosis. Double staining on rat lungs with the endothelial marker vWF and 8-oxo-2′-deoxyguanosine (8-oxo-dG), a marker of DNA oxidation, revealed that in vivo dasatinib treatment led to an increased expression of 8-oxo-dG in pulmonary ECs in comparison with vehicle-and imatinib-treated rats ( Figure 5A).…”
Section: Resultsmentioning
confidence: 99%
“…40 Geniposide inhibited the phosphorylation of downstream target GSK3β which was counteracted by preincubation with LY294002 along with increased expression of GLUT2 41 and restraining the adhesion of monocytes to HUVECs and the expression of CAMs induced by high glucose in treatment for diabetic vascular injury. 42 Ethanolic extract of Gardenia jasminoides inhibited TNF-alpha-induced NF-kappaB activation, adhesion molecule expression, and monocyte-endothelial interaction in the mechanism of treating vascular diseases, such as atherosclerosis. 43 Geniposide up-regulated the expression of foxp3, promoted Treg-cell-associated cytokines (TGF-β1 and IL-10) cells and ameliorated the atherosclerotic lesions progression partly through lipids regulation and immunoregulation 44 while its metabolite genipin suppressed the intracellular lipid accumulation and also significantly increased the intracellular expression of a fatty acid oxidation-related gene (peroxisomal proliferator-activated receptor: PPARα) so it was confirmed its anti--obesity, insulin resistance-alleviating and abnormal lipid metabolismalleviating effects.…”
Section: Anti-diabetic and Anti-atherosclerotic Activitiesmentioning
confidence: 99%